Karakteristik radiograf kista dentigerous dengan menggunakan CBCT-scan - Berty Pramatika; Aga Satria Nurrachman; Eha Renwi Astuti (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: The aim of this report which contains three case series is to describe the radiographic characteristic of dentigerous cyst using CBCT. Case Report: In the case presented here, all of the three patients had dentigerous cyst developing in impacted tooth, but did not have the same symptoms. CBCT radiography examination was carried out to find out the margin of the cortical extension, the diameter of the lesion, and the relations between the lesion and adjacent structures. The result of CBCT examination shows there is a variation of radiograph characteristics of dentigerous cyst among the three patients. Conclusion: CBCT is a very useful complementary tool for diagnosis and surgical planning in cases of dentigerous cyst, because three-dimensional viewing of the structures offers greater accuracy in lesion identification.